Dissolution Enhancement of Rosuvastatin Calcium by Liquisolid Compact Technique - Kapure, V. J. (J Pharm (Cairo), 2013)
In present investigation liquisolid compact technique is investigated as a tool for enhanced dissolution of poorly water-soluble drug Rosuvastatin calcium (RVT). The model drug RVT, a HMG-Co A reductase inhibitor was formulated in form of directly compressed tablets and liquisolid compacts; and studied for in-vitro release characteristics at different dissolution conditions. In this technique, liquid medications of water insoluble drugs in non-volatile liquid vehicles can be converted into acceptably flowing and compressible powders. Formulated systems were assessed for precompression parameters like flow properties of liquisolid system, Fourior transform infra red spectra (FTIR) analysis, X-ray powder diffraction (XRPD), differential scanning calorimetry (DSC), and post compression parameters like content uniformity, weight variation, hardness and friability, disintegration test, wetting time, in vitro dissolution studies, effect of dissolution volume on drug release rate, and estimation of fraction of molecularly dispersed drug in liquid medication. As liquisolid compacts demonstrated significantly higher drug release rates, we lead to conclusion that it could be a promising strategy in improving the dissolution of poor water soluble drugs and formulating immediate release solid dosage forms.